Inhibitory Effect of Apomorphine on Focal and Nonfocal Plasticity in the Human Motor Cortex - Fresnoza, Shane M. (Pharmaceutics, 2021)
Dopamine is crucial for neuroplasticity, which is considered to be the neurophysiological foundation of learning and memory. The specific effect of dopamine on plasticity such as long-term potentiation (LTP) and long-term depression (LTD) is determined by receptor subtype specificity, concentration level, and the kind of plasticity induction technique. In healthy human subjects, the dopamine precursor levodopa (L-DOPA) exerts a dosage-dependent non-linear effect on motor cortex plasticity. Low and high dosage L-DOPA impaired or abolished plasticity, while medium-dose preserved and reversed plasticity in previous studies. Similar dosage-dependent effects were also observed for selective D1-like and D2-like receptor activation that favor excitatory and inhibitory plasticity, respectively. However, such a dosage-dependent effect has not been explored for a nonselective dopamine agonist such as apomorphine in humans. To this aim, nonfocal and focal motor cortex plasticity induction using paired associative stimulation (PAS) and transcranial direct current stimulation (tDCS) were performed respectively in healthy participants under 0.1, 0.2, 0.3 mg apomorphine or placebo drug. Transcranial magnetic stimulation-elicited motor-evoked potentials were used to monitor motor cortical excitability alterations. We hypothesized that, similar to L-DOPA, apomorphine will affect motor cortex plasticity. The results showed that apomorphine with the applied dosages has an inhibitory effect for focal and nonfocal LTP-like and LTD-like plasticity, which was either abolished, diminished or reversed. The detrimental effect on plasticity induction under all dosages of apomorphine suggests a predominantly presynaptic mechanism of action of these dosages.